REKONSTRUKSI ASPEK BIOLOGIS DAN KONTEKS BUDAYA RANGKA MANUSIA HOLOSEN, SONG KEPLEK 5 - Sofwan Noerwidi (Balai Arkeologi Yogyakarta, 2012)
The Song Keplek 5 (SK5) specimen was found in 1998 at the Song Keplek site, located in the Gunung Sewu (Southern Mountains) karst region, East Java. SK5 is a burial dated within direct sample with an AMS date from its fragments bones of c. 3053 ± 65 calBP (AA96775). This paper will discuss the archaeological and biological context of SK 5. Biological information includes estimation of age, sex determination, height, and any indicators of systemic pathology. Discussion of archaeological context will include cultural practices during this individual’s life, and subsequent funerary practices post-mortem. This exploration of the cultural and biological context of SK 5 will not only begin to flesh out an “osteobiography” for this individual, but also improve our understanding of living conditions during the mid Holocene in Java, in the time of early Austronesian occupation in this island.